2019
DOI: 10.1002/jbio.201900004
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic assessment of hemodynamic changes in foot vessels

Abstract: Monitoring the blood supply in the lower extremities is critical for individuals who are vulnerable to vascular dysfunction. Current clinical approaches are ineffective in observing hemodynamic changes in peripheral vessels. In this paper, we investigate the potential of photoacoustic tomography (PAT) as an alternative way to in vivo monitor hemodynamic changes in foot vessels. High spatial and temporal resolution maps of hemoglobin in major arteries and veins are shown. Results from twelve human subjects are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Others vascular diagnostic imaging modalities, such as CTA, 70 nonenhanced MRA, 71,72 IVUS, 73 and the most recent emerging noninvasive US transducer array-based photoacoustic (optoacoustic) tomography (PTA), 74,75 are invoked to characterize anatomical details and morphologic characteristic of arterial lesion in diabetics lower limbs PAD. Generally, CTA and MRA are used in selected patients before revascularization to solve some specific questions caused by disagreement between previous imaging modalities and an existing particular clinical setting.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
“…Others vascular diagnostic imaging modalities, such as CTA, 70 nonenhanced MRA, 71,72 IVUS, 73 and the most recent emerging noninvasive US transducer array-based photoacoustic (optoacoustic) tomography (PTA), 74,75 are invoked to characterize anatomical details and morphologic characteristic of arterial lesion in diabetics lower limbs PAD. Generally, CTA and MRA are used in selected patients before revascularization to solve some specific questions caused by disagreement between previous imaging modalities and an existing particular clinical setting.…”
Section: Diagnostic Accuracymentioning
confidence: 99%
“…This type of study is feasible in humans. 22,28,29 A potential limitation of PAI is the depth penetration. Although imaging depth depends on optical and acoustic values of the tissue and can vary greatly, 22 depth penetration of 5 to 7 cm can be achieved and should be adequate for imaging calf muscles in humans.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The PAI technique has widely been used over the past decade for noninvasive cancer detection, diagnosis, and staging, [23][24][25] but its ability to monitor limb oxygenation and vascular dysfunction by peripheral arteries is in its infancy. [26][27][28][29] The goal of this study is to investigate the potential of PAI for evaluating oxygenation changes associated with PAD. As age is an independent unmodifiable risk factor, the study is performed in mice from different age cohorts to determine the differences in limb oxygenation with age.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, only a few examples of in vivo studies are conducted in the field of diabetes using PAT. In the work of Yang et al [201] it was shown that PAT has a potential in the diagnosis of vascular function (on the example of changes arising from arterial and venous occlusion).…”
Section: Optical Approaches In Diagnosticsmentioning
confidence: 99%